SOCIO-ECONOMIC RESILIENCE OF HOUSEHOLD IN THE COASTAL AREAS ON FLOOD DISASTERS (Case study of Coastal Areas affected by Flood Disaster caused by the Cempaka tropical storm in District Pacitan, East Java - Padmadi, Wijang
The coastal areas with great potentials, on the other hand, also face two major issues, are lagging of the socio-economic problems and the risk to disaster hazards. The experts opinion’s that by building community resilience, the two problems faced by people in the coastal areas such as the lagging of socio-economic and the high risk of disaster could be resolved. The concept of socio-economic resilience of household in the coastal areas which exist in recent literatures are still need further exploration. With case study of households on the coastal areas of District Pacitan which are affected by flood disaster caused by the Cempaka tropical storm, this research aims to find the effect of socio-economic of household characteristics to the level of household resilience on flood disasters. This research offers a new option in measuring of the community socio-economic resilience in the Indonesian coastal areas, on the household level with a quantitative approach using regression analysis with the MARS method to identify the household socio-economic factors that affect to the level of resilience. The level of household resilience is measured through an evaluation of the recent disaster impacts, which include: property damage, business loss, number of day disturbed activities, and speed of recovery time until the community is able to do the activities back to normal. Regression modeling using the MARS method obtains a model with 71.29 percent of determination value and the 83.33 percent of classification accuracy. This model identified two socio-economic factors that influence the level of household’s resilience on flood disaster in Pacitan coastal areas, are knowledge factor and work or income level factor.